Pharmacokinetic/pharmacodynamic integration of tilmicosin against Pasteurella multocida in a piglet tissue cage model - Chen, Yuqin; Ji, Xuan; Zhang, Suiling; Wang, Wenxiang; Zhang, Huilin; Ding, Huanzhong (Frontiers in Veterinary Science, 2023)
Tilmicosin is a semi-synthetic macrolide for veterinary use with strong antibacterial effect on respiratory bacteria. In this study, the pharmacokinetic/pharmacodynamic (PK/PD) integration of tilmicosin against Pasteurella multocida (P. multocida) was evaluated by establishing a piglet tissue cage infection model. Concentration of tilmicosin and bacterial numbers of P. multocida in the tissue-cage fluid were monitered. After the population of P. multocida was equal to or greater than 10 7 CFU/mL in a tissue cage, piglets received an oral administration of tilmicosin at a dose of 30, 40, 50, and 60 mg/kg b.w., once daily for 3 days, respectively. Bacteria were counted every 24 h after drug administration and at 48 and 72 h after the last administration. A sigmoidal Emax model was used to fit the relationship between PK/PD parameters and the antibacterial effect. AUC24h/MIC was the best PK/PD index that correlated with effectiveness of tilmicosin against P. multocida. The magnitude of AUC24h/MIC required for continuous 1/3-log, 1/2-log, and 3/4-log reductions were 19.65 h, 23.86 h, and 35.77 h, respectively, during each 24 h treatment period. In this study, when the dosage was > 50 mg/kg, the AUC24h/MIC was still > 35.77 h in the period of 24-48 h after the last administration due to the slow elimination, that is, tilmicosin exhibited a potent antibacterial effect against P. multocida after three successive daily administrations. The data provide meaningful guidance to optimize regimens of tilmicosin to treat respiratory tract infections caused by P. multocida.